Preparation method and application of compound traditional Chinese medicine drug-loaded hydrogel with hierarchical pore structure
By using materials such as carboxymethyl chitosan, sodium oxidized alginate and tanninic acid to prepare a multi-stage pore structure compound Chinese medicine hydrogel, it solves the problem of complex decoction and inappropriate long-term preservation, and achieves high-efficiency drug release and significant antibacterial effects.
Patent Information
- Application Number
- CN202510086551.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing Chinese medicine decoctions are complicated in the decoction process and are not suitable for long-term preservation, making it difficult to achieve rapid substance exchange and long-term release of Chinese medicine compound preparations.
Compound traditional Chinese medicine potable hydrogels with multi-stage porous structures were prepared by biopolysaccharide materials such as carboxymethyl chitosan, sodium oxidized alginate and tanninic acid. Porous structures were formed by NaBH4 treatment to improve drug release ability and antibacterial effect.
A multi-stage pore structure hydrogel with low toxicity and high biosafety is achieved, which significantly improves the drug release rate and antibacterial effect and simplifies the preparation process.
Smart Images

Figure CN119868256A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials and relates to a preparation method and application of a compound traditional Chinese medicine-loaded hydrogel with a multi-level pore structure. Background Art
[0002] In modern society, people's fast pace of life and unhealthy living habits can easily cause a series of chronic diseases, such as cardiovascular disease, diabetes, cancer, etc. These diseases often require long-term treatment and management, which seriously affect the quality of life of patients. For the treatment of such diseases, although Western medicine is effective quickly, long-term use will undoubtedly cause harm to the body. Traditional Chinese medicine has few toxic side effects and has good health care and preventive effects. Among them, the compound preparations of traditional Chinese medicine can make multiple traditional Chinese medicine ingredients synergistically enhance the efficacy. Some studies have shown that the active ingredients of some medicinal materials have interaction patterns. For example, Coptis chinensis and Scutellaria baicalensis are a pair of representative herbs traditionally used to treat gastrointestinal diseases. Berberine and baicalin in Coptis chinensis can be assembled into nanostructures in water, showing excellent antibacterial activity. There is a variety of evidence that Scutellaria baicalensis extract has a good therapeutic effect on colon inflammation, which has been confirmed in multiple models and clinical trials. Tannic acid is a natural polyphenol that exists in many traditional Chinese medicines such as red wine, black tea, green tea and rhubarb, and has a protective effect on acute or chronic intestinal inflammation. However, traditional Chinese medicine decoctions often have the disadvantages of complex decoction process and are not suitable for long-term storage. Therefore, combining hydrogel with compound preparations of traditional Chinese medicine can make up for the shortcomings of traditional Chinese medicine decoctions to a certain extent.
[0003] Carboxymethyl chitosan is a water-soluble polysaccharide derivative obtained by chemical modification of chitosan. Compared with chitosan, it has better water solubility, ion exchange capacity and biological activity. The amino groups in its molecular structure give it an active site for Schiff base reaction, which can react with a variety of compounds to form hydrogels. In addition, carboxymethyl chitosan has the advantages of biodegradability and biocompatibility, which makes it widely used in the biomedical field.
[0004] Compared with traditional hydrogels, porous hydrogels greatly improve the water absorption rate and water absorption ratio of hydrogels. The excellent properties of macroporous structure, air permeability and short diffusion path enable them to have the ability to quickly transmit media such as liquids, gases and biomolecule fixation. This is very beneficial for applications that require rapid material exchange, such as water treatment and biomedical applications.
[0005] Therefore, it is necessary to develop a new method to combine Chinese medicine compound preparations with hydrogels and obtain compound Chinese medicine-loaded hydrogel materials rich in multi-level pore structures. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides a drug-carrying system of a multi-level porous structure hydrogel compound Chinese medicine, and a preparation method and application thereof. The preparation method of the present invention is simple, and uses biopolysaccharide materials such as carboxymethyl chitosan, sodium alginate, and tannic acid, which have the characteristics of low toxicity and high biosafety, wherein tannic acid is used as a cross-linking agent and is also a natural medicine with excellent antibacterial ability. The hydrogel is formed into a multi-level porous structure by NaBH4 treatment, thereby having excellent drug release ability and can exert excellent antibacterial effect.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A compound traditional Chinese medicine-loaded hydrogel with a multi-level pore structure comprises the following components in parts by weight: 10-30 parts of carboxymethyl chitosan, 5-20 parts of oxidized sodium alginate, 3-5 parts of tannic acid, 0.5-1 part of baicalin, and 200-500 parts of water.
[0008] Preferably, the multi-level porous structure of the composite traditional Chinese medicine-loaded hydrogel is composed of the following components in parts by weight: 20 parts of carboxymethyl chitosan, 10 parts of carboxymethyl chitosan oxidized sodium alginate, 4 parts of tannic acid, 1 part of baicalin, and 200 parts of water.
[0009] The method for preparing the compound traditional Chinese medicine-loaded hydrogel with a multi-level pore structure comprises the following steps: (1) In solvent A, sodium alginate and an aqueous solution of sodium periodate are reacted to prepare oxidized sodium alginate; (2) dissolving carboxymethyl chitosan, tannic acid and baicalin in distilled water to obtain a mixed solution; dissolving the oxidized sodium alginate obtained in step (1) in distilled water to obtain an oxidized sodium alginate solution; and uniformly mixing the mixed solution and the oxidized sodium alginate solution, and allowing to stand at 4° C. to obtain a hydrogel.
[0010] (3) The hydrogel is immersed in a sodium borohydride solution to react and obtain a hydrogel with a hierarchical porous structure.
[0011] Preferably, in step (1), the solvent A is methanol, ethanol or acetone; further preferably, the solvent A is ethanol; the sodium alginate is added to the solvent A to obtain a sodium alginate suspension, and the mass ratio of the sodium alginate to the volume of the solvent A is 0.1-0.3 g / mL.
[0012] Preferably, in step (1), the volume ratio of the mass of sodium periodate in the sodium periodate aqueous solution to distilled water is 0.1-0.3 g / mL.
[0013] Further preferably, in step (1), the volume ratio of the sodium alginate suspension to the sodium periodate aqueous solution is 1:0.5-1.
[0014] Preferably, in step (1), the reaction temperature is room temperature, the reaction condition is to avoid light, and the reaction time is 6-18 h. More preferably, the reaction time is 10-12 h.
[0015] Preferably, in step (1), when the reaction is terminated, ethylene glycol in an amount equimolar to that of sodium periodate should be added.
[0016] Preferably, in step (1), after the reaction is completed, the reaction mixture should be poured into a large amount of vigorously stirred anhydrous ethanol, and the volume ratio of the reaction mixture to anhydrous ethanol is 1:5-8 to obtain a precipitate.
[0017] Further preferably, in step (1), the obtained precipitate is filtered and dried under vacuum at 40° C., and the obtained solid powder is dialyzed with distilled water for 24 h.
[0018] Preferably, in step (2), the mass ratio of carboxymethyl chitosan in the mixed solution to the volume ratio of distilled water is 0.1-0.3 g / mL; the mass ratio of tannic acid in the mixed solution to the volume ratio of distilled water is 0.04-0.08 g / mL; the mass ratio of baicalin in the mixed solution to the volume ratio of distilled water is 0.001-0.02 g / mL.
[0019] Preferably, according to the present invention, in step (2), the mass fraction of the oxidized sodium alginate solution is 5-10%.
[0020] Preferably, according to the present invention, in step (2), the volume ratio of the mixed solution to the oxidized sodium alginate solution is 1:0.5-1.5.
[0021] Preferably, according to the present invention, in step (3), the mass fraction of the sodium borohydride solution is 0.1-2%.
[0022] Preferably according to the present invention, in step (3), the reaction time is 2-5 min.
[0023] The application of the compound traditional Chinese medicine-loaded hydrogel with a multi-level pore structure in antibacterial materials.
[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The multi-level pore structure of the compound Chinese medicine-loaded hydrogel of the present invention has low toxicity and high biosafety. The carboxymethyl chitosan, oxidized sodium alginate, tannic acid, etc. used in the present invention are all biomaterials with the advantages of non-toxicity and high biocompatibility. The hydrogel extract was co-cultured with mouse fibroblasts (L929 cells) for 24 hours, and the cell survival rate was tested by CKK-8 experiment. The results showed that the multi-level pore structure of the compound Chinese medicine-loaded hydrogel of the present invention has low biotoxicity.
[0025] (2) The multi-level porous structure of the compound Chinese medicine-loaded hydrogel of the present invention has a good drug release effect. The present invention uses sodium borohydride treatment to make the gel have a porous structure, which has a better drug release effect. The gel was placed in a PBS solution and the amount of drug released after different time periods was measured. The results showed that the drug release rate of the hydrogel after sodium borohydride treatment was about twice that of the hydrogel not treated with sodium borohydride, and its release rate was also significantly higher than that of the untreated hydrogel.
[0026] (3) The multi-level porous structure of the compound Chinese medicine hydrogel loaded with medicine of the present invention has good antibacterial effect. The hydrogel-coated tannic acid / baicalin compound Chinese medicine prepared by the present invention has multiple effects such as antibacterial, anti-inflammatory, antioxidant, anti-tumor and antiviral, and has a wide range of pharmacological activities and clinical application potential. Staphylococcus aureus was evenly spread on the LB solid culture medium, the sterilized sample was attached to the surface of the culture medium, and was gently pressed with sterile tweezers to make the sample fully contact with the culture medium. The culture dish was placed in a constant temperature incubator at 37°C for 24 h. The antibacterial test results showed that the diameter of the antibacterial ring was about 28 mm, which had obvious antibacterial effect.
[0027] (4) The preparation method of the multi-level porous structure compound Chinese medicine loaded hydrogel of the present invention is simple. The hydrogel of the present invention is prepared by the Schiff base reaction between carboxymethyl chitosan and oxidized sodium alginate and the action of hydrogen bonds between carboxymethyl chitosan and tannic acid. It can be prepared within a few seconds of mixing at room temperature. The reaction conditions are mild and the operation process is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The scanning electron microscope images of the hydrogels prepared in Example 1 and Comparative Examples 1, 2, and 3; Figure 2 Electron microscope images of the hydrogels prepared in Example 1 and Comparative Examples 1, 2, and 3; Figure 3 This is a comparison chart of the drug release rates of the hydrogels in Example 1 and Comparative Example 1 in simulated body fluids with different pH values; Figure 4 This is a comparison chart of the drug release rates of the hydrogels in Comparative Example 2 and Comparative Example 3 in simulated body fluids with different pH values; Figure 5 Graph showing cell survival rates of hydrogels prepared in Example 1 and Comparative Examples 1-3; Figure 6 The graph is a graph showing the antibacterial test results of the hydrogels of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3. DETAILED DESCRIPTION
[0029] The present invention is further described below with reference to specific embodiments, but is not limited thereto.
[0030] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0031] Example 1 A drug-carrying system of a multi-level porous structure hydrogel compound traditional Chinese medicine and a preparation method thereof, the preparation method comprising the following steps: (1) Preparation of aldehyde-modified sodium alginate (OSA): Disperse 10 g of sodium alginate in 50 mL of anhydrous ethanol to prepare suspension Ⅰ. Dissolve 10 g of sodium periodate in 50 mL of water to prepare solution Ⅱ. Add solution Ⅱ to suspension Ⅰ, stir magnetically at room temperature in the dark overnight, and add ethylene glycol in an amount equimolar to sodium periodate to terminate the reaction. Pour the reaction mixture into a large amount of anhydrous ethanol with vigorous stirring (V(reaction mixture):V(ethanol)=1∶5) to precipitate. Filter and dry in vacuum at 40 ℃. The obtained solid powder is dialyzed with distilled water for 24 h to remove unreacted sodium periodate and small molecular impurities such as ethylene glycol. The liquid in the dialysis bag is freeze-dried to obtain a white flocculent product, which is aldehyde-modified sodium alginate.
[0032] (2) Preparation of hydrogel drug delivery system: Dissolve 0.1 g of carboxymethyl chitosan, 0.02 g of tannic acid and 0.005 g of baicalin in 0.5 mL of distilled water, referred to as solution IV. Dissolve 1 g of the aldehyded sodium alginate prepared in step (1) in 9 g of distilled water to prepare a aldehyded sodium alginate solution with a mass concentration of 10%. Mix solution IV and the 10% aldehyded sodium alginate solution in equal proportions and let stand at 4 °C to obtain a hydrogel.
[0033] (3) The hydrogel prepared in step (2) was immersed in 1% NaBH4 for 5 min to obtain a hydrogel with a hierarchical pore structure.
[0034] The multi-level porous structure hydrogel is composed of the following components in parts by weight: 20 parts of carboxymethyl chitosan, 10 parts of oxidized sodium alginate, 4 parts of tannic acid, 1 part of baicalin, and 200 parts of water.
[0035] Example 2 A drug-carrying system of a multi-level porous structure hydrogel compound traditional Chinese medicine and a preparation method thereof, the preparation method comprising the following steps: (1) Preparation of aldehyde-modified sodium alginate (OSA): Disperse 10 g of sodium alginate in 50 mL of anhydrous ethanol to prepare suspension Ⅰ. Dissolve 10 g of sodium periodate in 50 mL of water to prepare solution Ⅱ. Add solution Ⅱ to suspension Ⅰ, stir magnetically at room temperature in the dark overnight, and add ethylene glycol in an amount equimolar to sodium periodate to terminate the reaction. Pour the reaction mixture into a large amount of anhydrous ethanol with vigorous stirring (V(reaction mixture):V(ethanol)=1∶5) to precipitate. Filter and dry in vacuum at 40 ℃. The obtained solid powder is dialyzed with distilled water for 24 h to remove unreacted sodium periodate and small molecular impurities such as ethylene glycol. The liquid in the dialysis bag is freeze-dried to obtain a white flocculent product, which is aldehyde-modified sodium alginate.
[0036] (2) Preparation of hydrogel drug delivery system: Dissolve 0.1 g of carboxymethyl chitosan, 0.04 g of tannic acid and 0.005 g of baicalin in 0.5 mL of distilled water, referred to as solution IV. Dissolve 1 g of the aldehyded sodium alginate prepared in step (1) in 9 g of distilled water to prepare a aldehyded sodium alginate solution with a mass concentration of 10%. Mix solution IV and the 10% aldehyded sodium alginate solution in equal proportions and let stand at 4 °C to obtain a hydrogel.
[0037] (3) The hydrogel prepared in step (2) was immersed in 1% NaBH4 for 5 min to obtain a hydrogel with a hierarchical pore structure.
[0038] The multi-level porous structure hydrogel is composed of the following components in parts by weight: 20 parts of carboxymethyl chitosan, 10 parts of oxidized sodium alginate, 5 parts of tannic acid, 1 part of baicalin, 200 parts of water Example 3 A drug-carrying system of a multi-level porous structure hydrogel compound traditional Chinese medicine and a preparation method thereof, the preparation method comprising the following steps: (1) Preparation of aldehyde-modified sodium alginate (OSA): Disperse 10 g of sodium alginate in 50 mL of anhydrous ethanol to prepare suspension Ⅰ. Dissolve 10 g of sodium periodate in 50 mL of water to prepare solution Ⅱ. Add solution Ⅱ to suspension Ⅰ, stir magnetically at room temperature in the dark overnight, and add ethylene glycol in an amount equal to that of sodium periodate to terminate the reaction. Pour the reaction mixture into a large amount of anhydrous ethanol with vigorous stirring (V(reaction mixture):V(ethanol)=1∶5) to precipitate. Filter and dry in vacuum at 40 ℃. The obtained solid powder is dialyzed with distilled water for 24 h to remove unreacted sodium periodate and small molecular impurities such as ethylene glycol. Freeze-dry the liquid in the dialysis bag to obtain a white flocculent product, which is aldehyde-modified sodium alginate.
[0039] (2) Preparation of hydrogel drug delivery system: Dissolve 0.1 g of carboxymethyl chitosan, 0.02 g of tannic acid and 0.005 g of baicalin in 0.5 mL of distilled water, referred to as solution IV. Dissolve 0.5 g of the aldehyded sodium alginate prepared in step (1) in 9.5 g of distilled water to prepare a aldehyded sodium alginate solution with a mass concentration of 5%. Mix solution IV and the 5% aldehyded sodium alginate solution in equal proportions and let stand at 4°C to obtain a hydrogel.
[0040] (3) The hydrogel prepared in step (2) was immersed in 1% NaBH4 for 5 min to obtain a hydrogel with a hierarchical pore structure.
[0041] The multi-level porous structure hydrogel is composed of the following components in parts by weight: 20 parts of carboxymethyl chitosan, 5 parts of oxidized sodium alginate, 4 parts of tannic acid, 1 part of baicalin, and 205 parts of water.
[0042] Comparative Example 1 A drug-carrying system of a multi-level porous structure hydrogel compound Chinese medicine and a preparation method thereof, comprising the steps of: (1) Preparation of aldehyde-modified sodium alginate (OSA): Disperse 10 g of sodium alginate in 50 mL of anhydrous ethanol to prepare suspension Ⅰ. Dissolve 10 g of sodium periodate in 50 mL of water to prepare solution Ⅱ. Add solution Ⅱ to suspension Ⅰ, stir magnetically at room temperature in the dark overnight, and add ethylene glycol in an amount equimolar to sodium periodate to terminate the reaction. Pour the reaction mixture into a large amount of anhydrous ethanol with vigorous stirring (V(reaction mixture):V(ethanol)=1∶5) to precipitate. Filter and dry in vacuum at 40℃. The obtained solid powder is dialyzed with distilled water for 24 h to remove unreacted sodium periodate and small molecular impurities such as ethylene glycol. The liquid in the dialysis bag is freeze-dried to obtain a white flocculent product, which is aldehyde-modified sodium alginate.
[0043] (2) Preparation of hydrogel drug delivery system: Dissolve 0.1 g of carboxymethyl chitosan, 0.02 g of tannic acid and 0.005 g of baicalin in 0.5 mL of distilled water, referred to as solution III. Dissolve 1 g of the aldehyded sodium alginate prepared in step (1) in 9 g of distilled water to prepare a aldehyded sodium alginate solution with a mass concentration of 10%. Mix solution III and the 10% aldehyded sodium alginate solution in equal proportions and let stand at 4 °C to obtain a hydrogel.
[0044] Comparative Example 2 A drug-carrying system for a hydrogel compound traditional Chinese medicine and a preparation method thereof, comprising the steps of: (1) Preparation of aldehyde-modified sodium alginate (OSA): Disperse 10 g of sodium alginate in 50 mL of anhydrous ethanol to prepare suspension Ⅰ. Dissolve 10 g of sodium periodate in 50 mL of water to prepare solution Ⅱ. Add solution Ⅱ to suspension Ⅰ, stir magnetically at room temperature in the dark overnight, and add ethylene glycol in an amount equimolar to sodium periodate to terminate the reaction. Pour the reaction mixture into a large amount of anhydrous ethanol with vigorous stirring (V(reaction mixture):V(ethanol)=1∶5) to precipitate. Filter and dry in vacuum at 40℃. The obtained solid powder is dialyzed with distilled water for 24 h to remove unreacted sodium periodate and small molecular impurities such as ethylene glycol. Freeze-dry the liquid in the dialysis bag to obtain a white flocculent product, which is aldehyde-modified sodium alginate.
[0045] (2) Preparation of hydrogel drug delivery system: Dissolve 0.1 g of carboxymethyl chitosan and 0.02 g of tannic acid in 0.5 mL of distilled water, referred to as solution III. Dissolve 1 g of the aldehyded sodium alginate prepared in step (1) in 9 g of distilled water to prepare a aldehyded sodium alginate solution with a mass concentration of 10%. Mix solution III and the 10% aldehyded sodium alginate solution in equal proportions and let stand at 4 °C to obtain a hydrogel.
[0046] (3) The hydrogel prepared in step (2) was immersed in 1% NaBH4 for 5 min to obtain a hydrogel with a hierarchical pore structure.
[0047] Comparative Example 3 A drug-carrying system for a hydrogel compound traditional Chinese medicine and a preparation method thereof, comprising the steps of: (1) Preparation of aldehyde-modified sodium alginate (OSA): Disperse 10g of sodium alginate in 50mL of anhydrous ethanol to prepare suspension Ⅰ. Dissolve 10g of sodium periodate in 50mL of water to prepare solution Ⅱ. Add solution Ⅱ to suspension Ⅰ, stir magnetically at room temperature in the dark overnight, and add ethylene glycol in an amount equimolar to sodium periodate to terminate the reaction. Pour the reaction mixture into a large amount of anhydrous ethanol with vigorous stirring (V(reaction mixture):V(ethanol)=1∶5) to precipitate. Filter and dry in vacuum at 40℃. The obtained solid powder is dialyzed with distilled water for 24h to remove unreacted sodium periodate and small molecular impurities such as ethylene glycol. Freeze-dry the liquid in the dialysis bag to obtain a white flocculent product, which is aldehyde-modified sodium alginate.
[0048] (2) Preparation of hydrogel drug delivery system: Dissolve 0.1 g of carboxymethyl chitosan and 0.02 g of tannic acid in 0.5 mL of distilled water, referred to as solution IV. Dissolve 1 g of the aldehyded sodium alginate prepared in step (1) in 9 g of distilled water to prepare a aldehyded sodium alginate solution with a mass concentration of 10%. Mix solution IV and the 10% aldehyded sodium alginate solution in equal proportions and let stand at 4 °C to obtain a hydrogel.
[0049] Porous structure materials have advantages such as high specific surface area and strong permeability and adsorption in daily life and production. In order to verify the internal structure of the hydrogel sample, the present invention carried out SEM and optical microscope tests.
[0050] Test example: Microstructure of hydrogel like Figure 1 As shown in, (a), (b), (c), and (d) correspond to the microscopic SEM images of the hydrogels in Example 1 and Comparative Examples 1-3, respectively. Figure 1 (a)-(d) show the scanning electron microscope images of COT@BC@NaBH4 (Example 1), COT@NaBH4 (Comparative Example 2), COT@BC (Comparative Example 1) and COT (Comparative Example 3) hydrogel samples, COT is carboxymethyl chitosan / oxidized sodium alginate / tannic acid hydrogel, BC is baicalin. All four hydrogels have a porous network structure. However, it can be observed that Figure 1 In (a) and (b), the number of pores in COT@BC@NaBH4 and COT@NaBH4 is significantly greater than that in COT@BC and COT, and they are denser and have smaller pore sizes. Therefore, it can be inferred that the treatment with NaBH4 will affect the porous structure of the hydrogel and make it have a denser pore structure. Figure 1 Comparison between (a) and (b), and (c) and (d) shows that the baicalin-loaded hydrogel exhibits a smaller internal pore structure, indicating that baicalin has been successfully dispersed in the hydrogel.
[0051] like Figure 2 As shown in, (a), (b), (c), and (d) correspond to the optical microscope images of the hydrogels in Example 1 and Comparative Examples 1-3, respectively. From the comparison of the gel images under an optical microscope, it can be seen that after the sodium borohydride treatment, many large pores are generated inside the gel, forming a multi-level pore structure on the basis of the porous structure of the hydrogel itself.
[0052] Performance test of hydrogel adsorbent: (1) In vitro drug release performance test of hydrogel The hydrogels prepared in Example 1 and Comparative Example 1 were placed in PBS solutions with pH values of 3 / 5 / 7, respectively, and the PBS solutions were taken out at intervals to test their ultraviolet absorbance. A standard curve was established to calculate the drug release rate. The test results are shown in Figure 3 .
[0053] Depend on Figure 3 It can be seen that the release rate and release ratio of the hydrogel prepared in Example 1 are higher than those of the hydrogel prepared in Comparative Example 1. Figure 3It can be seen that the prepared hydrogel has pH-responsive properties, and the release rate under neutral conditions is higher than that under acidic conditions.
[0054] Figure 4 This is a comparison chart of the drug release rates of the hydrogels in Comparative Example 2 and Comparative Example 3 in simulated body fluids with different pH values, indicating that the drug release rate of the hydrogel treated with sodium borohydride is significantly higher than that of the hydrogel not treated with sodium borohydride.
[0055] (2) Biological toxicity test of hydrogel The hydrogel extract was co-cultured with mouse fibroblasts (L929 cells) for 24 h, and the cell survival rate was tested by CKK-8 assay. Figure 5 As shown in , the cell survival rate is the ratio of the experimental group to the blank sample: the compound Chinese medicine-loaded hydrogel with multi-level pore structure of the present invention has low biological toxicity. The blank sample is a mouse fibroblast culture sample without adding hydrogel extract.
[0056] (3) Antibacterial property test of hydrogel LB liquid culture medium - Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 2.5 g of LB broth culture medium and add it to mix well. Sterilize it in a high-temperature and high-pressure steam sterilizer at 121°C for 15 min and set it aside for use.
[0057] LB solid culture medium - Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 2.5 g of LB broth culture medium and 1.5 g of agar powder. Add the above weighed reagents and mix well. Sterilize in a high-temperature and high-pressure steam sterilizer at 121°C for 15 minutes. When the culture medium cools to about 40-50°C, use an electric pipette to draw 15 mL of the culture medium and pour it into a disposable sterile plate.
[0058] Take two 12 mL bacterial culture tubes, add 3 mL LB liquid culture medium to each, pick a single colony from the solid culture medium of Staphylococcus aureus and add it to the liquid culture medium, and use the other tube as a blank control. Place in a constant temperature shaker (37 ℃, 200 rpm) and shake culture overnight (15 h).
[0059] Dilute the Staphylococcus aureus solution to 10 6CFU / mL, then draw 100 μL and evenly spread it on the LB solid culture medium. The sterilized samples (Example 1 and Comparative Example 1) were attached to the surface of the culture medium respectively, and gently pressed with sterile tweezers to make the sample fully contact with the culture medium. The culture dish was placed in a constant temperature incubator at 37 °C for 24 hours. After the culture was completed, it was taken out and photographed with an ordinary camera and the size of the inhibition zone was measured and recorded. The test results are shown in Figure 6 , wherein (a), (b), (c), and (d) correspond to the antibacterial ring photos of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively.
[0060] Depend on Figure 6 It can be seen that the diameter of the inhibition zone of Example 1 is significantly higher than that of Comparative Example 1, which proves that it has a higher antibacterial effect.
Claims
1. A compound Chinese medicine-loaded hydrogel with a multi-level pore structure, characterized in that: The invention comprises the following components in parts by weight: 10-30 parts of carboxymethyl chitosan, 5-20 parts of oxidized sodium alginate, 3-5 parts of tannic acid, 0.5-1 part of baicalin and 200-500 parts of water.
2. The multi-level porous structure of the compound traditional Chinese medicine loaded hydrogel according to claim 1, characterized in that: The multi-level porous structure of the compound traditional Chinese medicine-loaded hydrogel is composed of the following components in parts by weight: 20 parts of carboxymethyl chitosan, 10 parts of carboxymethyl chitosan oxidized sodium alginate, 4 parts of tannic acid, 1 part of baicalin, and 200 parts of water.
3. The method for preparing the compound Chinese medicine-loaded hydrogel with a multi-level pore structure according to claim 1 or 2, characterized in that: The following steps are involved: (1) In solvent A, sodium alginate and an aqueous solution of sodium periodate are reacted to prepare oxidized sodium alginate; (2) dissolving carboxymethyl chitosan, tannic acid and baicalin in distilled water to obtain a mixed solution; dissolving the oxidized sodium alginate obtained in step (1) in distilled water to obtain an oxidized sodium alginate solution; and uniformly mixing the mixed solution and the oxidized sodium alginate solution, and allowing to stand at 4° C. to obtain a hydrogel. (3) The hydrogel is immersed in a sodium borohydride solution to react, thereby obtaining a compound Chinese medicine-loaded hydrogel with a multi-level pore structure.
4. The method for preparing the compound Chinese medicine-loaded hydrogel with a multi-level pore structure according to claim 3, characterized in that: In step (1), the solvent A is methanol, ethanol or acetone; preferably, the solvent A is ethanol; the sodium alginate is added to the solvent A to obtain a sodium alginate suspension, and the mass ratio of the sodium alginate to the volume of the solvent A is 0.1-0.3 g / mL.
5. The method for preparing the compound Chinese medicine-loaded hydrogel with a multi-level pore structure according to claim 4, characterized in that: In step (1), the volume ratio of the mass of sodium periodate in the sodium periodate aqueous solution to distilled water is 0.1-0.3 g / mL; preferably, in step (1), the volume ratio of the sodium alginate suspension to the sodium periodate aqueous solution is 1:(0.5-1).
6. The method for preparing the compound Chinese medicine-loaded hydrogel with a multi-level pore structure according to claim 3, characterized in that: In step (1), the reaction temperature is room temperature, the reaction condition is to avoid light; the reaction time is 6-18 h; preferably, the reaction time is 10-12 h.
7. The method for preparing the compound Chinese medicine-loaded hydrogel with a multi-level pore structure according to claim 3, characterized in that: In step (1), when the reaction is terminated, ethylene glycol in an amount equimolar to sodium periodate should be added; Preferably, in step (1), after the reaction is completed, the reaction mixture should be poured into vigorously stirred anhydrous ethanol, and the volume ratio of the reaction mixture to anhydrous ethanol is 1:(5-8) to obtain a precipitate; Preferably, in step (1), the obtained precipitate is filtered and dried under vacuum at 40° C., and the obtained solid powder is dialyzed with distilled water for 24 h.
8. The method for preparing the compound Chinese medicine-loaded hydrogel with a multi-level pore structure according to claim 3, characterized in that: In step (2), the mass ratio of carboxymethyl chitosan in the mixed solution to the volume ratio of distilled water is 0.1-0.3 g / mL; the mass ratio of tannic acid in the mixed solution to the volume ratio of distilled water is 0.04-0.08 g / mL; the mass ratio of baicalin in the mixed solution to the volume ratio of distilled water is 0.001-0.02 g / mL; Preferably, in step (2), the mass fraction of the oxidized sodium alginate solution is 5-10%; further preferably, in step (2), the volume ratio of the mixed solution to the oxidized sodium alginate solution is 1:0.5-1.
5.
9. The method for preparing the compound Chinese medicine-loaded hydrogel with a multi-level pore structure according to claim 3, characterized in that: In step (3), the mass fraction of the sodium borohydride solution is 0.1-2%; preferably, in step (3), the reaction time is 2-5 min.
10. Use of the compound traditional Chinese medicine-loaded hydrogel with a multi-level pore structure according to claim 1 or 2 in antibacterial materials.
Citation Information
Patent Citations
Injectable and rapidly-gelatinized composite hydrogel and preparation method thereof
CN110201219A
Antibacterial compound hydrogel and preparation method thereof
CN111150880A
Method for preparing chitosan-porous starch compound by chemical grafting method and application of chitosan-porous starch compound in no-wash hair care product
CN115926176A
Chitosan-sodium alginate hydrogel, preparation method and application thereof, copper peroxide-containing hydrogel and preparation method thereof
CN116425999A